User embracement: the nurses' perception in a urgency and emergency unit - Natália Mendes Malta Rodrigues Costa; Rejane Cussi Assunção Lemos; Poliana Silva de Oliveira; Gisele Bento Sgotti (Universidade Federal de Santa Maria, 2018)
Aim: to identify nurse's perception about the user´s adjustment and to analyze its articulation with the fundamentals of the National Humanization Policy (PNH). Method: qualitative research, with 14 nurses working in the Adult Emergency Department of the Hospital das Clínicas of the Federal University of Triângulo Mineiro. Datas were collected in December 2015, through a semi-structured interview and analyzed according to content analysis. Results: the following categories emerged: the user embracement as initial service, where it is described as action on the user's entry into the service; humanization, demonstrating understanding and application according to the PNH; difficulties in developing the user embracement due to overwork, lack of flow and infrastructure. Conclusions: the nurses demonstrated to understand the meaning of the user embracement. However, there are weak aspects in the applicability, which deserves the attention of health managers to ensure that the principles of PNH are guaranteed.